Personal aspects that affect the digital competence of university teachers in Perú - López-Armes, Edy Luisa (AiBi Journal of Research, Administration and Engineering, 2025)
This research sought to establish whether there is a relationship between personal characteristics and the digital skills of university teachers in Peru. We chose to work with the quantitative type. The descriptive correlational design was applied. It was collected by means of a questionnaire instrument with 42 questions on a five-level Likert scale, which previously had the respective validity and reliability. The information was processed with percentage data, frequency tables and graphs. A Spearman’s Rho test analysis was performed with SPSS software, which evaluated the relationship between two random variables, one continuous and the other discrete. A teacher’s digital skills are determined by personal factors such as age, area of specialization, employment status, amount of time in service and access to technological equipment. It was found that the degree of digital skills of university teachers is intermediate, reaching 58%. This also applies to the dimensions of communication, collaboration and digital security, digital content creation and problem solving. There is a positive correlation between individual factors and the digital skills of university teachers.